Utilization of oil contaminated sand for green asphalt concrete production - Ng, Ye Han (2015)
Managing of Oil Contaminated Sand (OCS) has been an issue in many countries especially Singapore as one of the largest oil refinery industry. One of the major challenge faced on OCS is the high treatment cost. To address this issue, many studies have been conducted with the possibility of using OCS as construction material. The objective of this research is to study the feasibility of Oil Contaminated Sand (OCS) usage as a replacement of certain percentage of fine aggregates in Hot Mix Asphalt (HMA) for road construction. Besides investigating the use of OCS in HMA, the effects of incorporating Recycled Concrete aggregates (RCA) as a replacement of certain percentage of coarse aggregates with OCS on the asphalt mixture were also examined. Three mix designs incorporating with 20%, 30% and 40% OCS replacement and one mix design with the mixture of RCA (coarse) and OCS (fines) were evaluated and comparison were made against one another. A series of experimental test, namely Marshall Stability, Retained Marshall Stability, Indirect Tensile and Dynamic Creep test were conducted to assess the strength and durability of the asphalt concrete. Experimental results showed a good indication of the feasibility to replace fine aggregates with OCS up to 20% and also found that the effect of incorporating coarse RCA is not as significant as incorporating of OCS in HMA. The success of this research indicates the feasible use of 20% OCS with incorporating coarse RCA as a replacement material for coarse and fine granite in HMA applications for green asphalt concrete production.